Rational Design of a ZnII MOF with Multiple Functional Sites for Highly Efficient Fixation of CO2 under Mild Conditions: Combined Experimental and Theoretical Investigation. Issue 72 (1st December 2020) - Das, Rajesh; Muthukumar, D.; Pillai, Renjith S.; Nagaraja, C. Mallaiah
Abstract: The development of efficient heterogeneous catalysts suitable for carbon capture and utilization (CCU) under mild conditions is a promising step towards mitigating the growing concentration of CO2 in the atmosphere. Herein, we report the construction of a hydrogen‐bonded 3D framework, [Zn(hfipbba)(MA)]⋅3 DMF n (hfipbba=4, 4′‐(hexaflouroisopropylene)bis(benzoic acid)) (HbMOF1 ) utilizing Zn II center, a partially fluorinated, long‐chain dicarboxylate ligand (hfipbba), and an amine‐rich melamine (MA) co‐ligand. Interestingly, the framework possesses two types of 1D channels decorated with CO2 ‐philic (−NH2 and −CF3 ) groups that promote the highly selective CO2 adsorption by the framework, which was supported by computational simulations. Further, the synergistic involvement of both Lewis acidic and basic sites exposed in the confined 1D channels along with high thermal and chemical stability rendered HbMOF1 a good heterogeneous catalyst for the highly efficient fixation of CO2 in a reaction with terminal/internal epoxides at mild conditions (RT and 1 bar CO2 ). Moreover, in‐depth theoretical studies were carried out using periodic DFT to obtain the relative energies for each stage involved in the catalytic reaction and an insight mechanistic details of the reaction is presented. Overall, this work represents a rare demonstration of rational design of a porous Zn II MOF incorporating multiple functional sites suitable for highly efficient fixation of CO2 with terminal/internal epoxides at mild conditions supported by comprehensive theoretical studies. Abstract : Terminal catch : The rational design of a porous Zn II metal–organic framework (MOF) incorporating multiple functional sites suitable for highly efficient fixation of CO2 with terminal/internal epoxides under mild conditions supported by comprehensive theoretical studies to provide insight on the mechanistic details of the catalytic process is presented.